Assessment of the degree of preparation for the challenge of internationalization of SMEs from an integrative approach to the dynamic capabilities and knowledge management [Evaluación del grado de preparación para asumir el reto de la internacionalización de las pymes desde un enfoque integrador de las capacidades dinámicas y la gestión del conocimiento] (2015)
This paper presents a case study of two SMEs companies, one of the traditional type and the other based on knowledge. Its purpose is to establish whether there is any type of relationship between a tool that evaluates the degree of preparation for internationalization from the perspective of dynamic capabilities and one that takes the conceptual elements of the ambidextrous organization to diagnose the state of knowledge management of these productive organizations. The methodology describes how the two tools are structured to the junction of their measurements, whose specific purpose is to identify the nodal matters that allow the entrepreneur-owner of the SME to reduce the risks of its internationalization process. With this exploratory study is expected to advance the state of the art of these themes providing solid foundations for future work that would allow the construction of a more complete understanding of the phenomenon of internationalization of SMEs.